Who is adjusting to whom?: Differences in elephant diel activity in wildlife corridors across different human-modified landscapes - Adams, Tempe S. F.; Leggett, Keith E.A.; Chase, Michael J.; Tucker, Marlee A. (Frontiers in Conservation Science, 2022)
The global impact of increased human activities has consequences on the conservation of wildlife. Understanding how wildlife adapts to increased human pressures with urban expansion and agricultural areas is fundamental to future conservation plans of any species. However, there is a belief that large wild free-ranging carnivores and ungulates, cannot coexist with people, limited studies have looked at wildlife movements through differing human-dominated landscapes at finer spatial scales, in Africa. This information is vital as the human population is only going to increase and the wildlife protected areas decrease. We used remote-sensor camera traps to identify the movement patterns of African elephant (Loxodonta africana) through six wildlife corridors in Botswana. The wildlife corridors were located in two different human-dominated landscapes (agricultural/urban), with varying degrees of human impact. While we found that elephants use corridors in both landscapes, they use the urban corridors both diurnally and nocturnally in contrast to agricultural corridors which were only nocturnal. Our results provide evidence for temporal partitioning of corridor use by elephants. We identified that seasonality and landscape were important factors in determining the presence of elephants in the corridors. Our findings demonstrate that elephant diel patterns of use of the wildlife corridor differs based on the surrounding human land-uses on an hourly basis and daily basis, revealing potential adaptation and risk avoidance behaviour.